Agile governance theory - LUNA, Alexandre José Henrique de Oliveira (2015)
Context: Competitiveness is the key to a sustainable development and it demands agility at the business and organizational levels, which in turn requires a flexible and customizable Information Technology (IT) environment, as well as an effective and responsive governance in order to deliver value faster, better, and cheaper to the business. Objective: This PhD thesis describes the research conducted to analyze and better understand this context, and which result is a theory to analyze and describe agile governance (AG). We assumed that once the agile governance phenomena are better understood, by means of the mapping of their constructs, mediators, moderators and disturbing factors, this achievement can help people and organizations reach better results in their application: reducing cost and time, increasing the quality and success rate of their practice. Method: We conducted a systematic literature review about the state of the art of agile governance, together with observation and interaction on professional groups based on social networks, and semi-structured interviews with representative agents of the phenomena in study. We have applied comparative and structuralist methods of procedures and have used some techniques of Grounded Theory to synthetize the collected data. We have also formatted the emerging theory by the Dubin’s quantitative method of theory building for applied disciplines, and operationalized it for testing, by means of Structural Equation Modeling (SEM). Results: As a result, we could offer the phenomena characterization, a convergent definition for agile governance, six meta principles, nine metavalues and a map of findings organized by topic and classified by relevance and convergence. We have developed a conceptual framework of the theory encompassing: its constructs, laws of interaction, boundaries and system states. Further, we have also operationalized the emerging theory: identifying its propositions, deriving empirical indicators from its constructs and establishing testable hypotheses to assess theory plausibility in eight theoretical scenarios, through an empirical study, by means of an explanatory survey with representative agents from phenomena under study. We had a response rate around 29.4% (obtained by the ratio of 281 responses out of 956 invitations), as well as an effective response rate around 12.3% (118 valid cases for statistical analysis, having a broad geographical coverage). The Confirmatory Factor Analysis (CFA) and SEM Analysis point out the plausibility of the theory components and hypotheses. Conclusion: The results present evidences of the theory plausibility, indicating that further studies are necessary to reach a trustworthy theory to analyze and describe the agile governance phenomena. At same time, lessons learned derived from this study, about the amplitude of the phenomena under study and the particularity of each subsample, suggest that the data collection instrument shall be tailored according to (i) each organizational context, (ii) suitable theoretical scenario, and (iii) chaos and order scale, in order to obtain more accurate data to analyze its: generalization, causality, explanation, and prediction. We expect that the emerging theory can provide some insights to understand agile governance phenomena and consequently help to achieve the necessary fluency in this area of knowledge in order to bring it to a new level, accelerating its development by scholars and practitioners. Eventually, we have made improvements and additions to the methodological approach for exploratory qualitative and quantitative studies.